A numerical study of the mixing and stratification alterations in estuaries due to climate change using the potential energy anomaly - Lupiola, Jagoba; Bárcena, Javier F.; García-Alba, Javier; García, Andrés (Frontiers in Marine Science, 2023)
The competition between mixing and stratification in estuaries determines the quality of their waters, living conditions, and uses. These processes occur due to the interaction between tidal and fluvial contributions, which significantly vary depending on the estuarine characteristics. For the study of mixing and stratification alterations in estuaries due to climate change, a new methodology is proposed based on high-resolution 3D hydrodynamic modeling to compute the Potential Energy Anomaly (). is defined as the amount of energy required to homogenize the water column, i.e., indicates the intensity of stratification. Therefore, the spatiotemporal evolution of stratification is calculated by analyzing the estuary with a detailed grid during a complete year. Regarding the model scenarios, first, a base case is analyzed with the realistic forcings of the year 2020, from which the functioning of the estuary is obtained. Subsequently, the forecasts of anomalies due to climate change for sea conditions (level, temperature, and salinity), atmosphere conditions (precipitation, air temperature, relative humidity, and solar irradiance), and river conditions (flow and temperature) are projected on the year 2020. The selected scenarios to analyze hydrodynamic changes are RCP 4.5 and 8.5 for the years 2050 and 2100, respectively. The proposed methodology has been applied to the Suances estuary, where due to climate change, the mixing and stratification conditions will be modified by the increased intrusion of marine waters into the estuary, generating a change in the biodiversity of the intertidal areas. Moreover, the climate change effects will tend to increase the intensity of stratification upstream of the estuary and decrease downstream.